Toxicokinetics of Nanoparticles Deposited in Lungs Using Occupational Exposure Scenarios - Creutzenberg, Otto; Pohlmann, Gerhard; Schaudien, Dirk; Kock, Heiko (Frontiers in Public Health, 2022)
Various synthetic powders with primary particle sizes at the nanoscale and a high commercial impact have been studied using Wistar rats. The test materials were metal oxides, i.e., TiO2, ZnO and amorphous silica, and carbon black (technical soot). Dosing schemes were in the regular ranges typically used in subacute rat studies to simulate occupational exposure scenarios (mg range). Nanoscaled particle agglomerates have the potential to disintegrate and translocate as individual nanoparticles to remote locations following deposition in the lungs. The toxicokinetic fate of metal oxides post-inhalation in lungs/organs was investigated (i) by chemical analysis of the retained particulate/dissolved matter and (ii) by visualization of particles in various remote organs using transmission electron microscopy (TEM). The three titanium dioxides (NM-103, NM-104, NM-105; JRC coding) showed a very slow dissolution in lung fluids. In contrast, the coated ZnO (NM-111) dissolved quickly and was eliminated from the body within approximately 1 day. The precipitated amorphous silica (NM-200) showed a partial dissolution. Chemical analysis in lungs (particulate and soluble TiO2) and in remote organs (liver and brain) showed a small solubility effect under physiological conditions. The translocation to remote organs was negligible. This confirms that for poorly soluble TiO2 particles there was no considerable translocation to the liver and brain. The chemical analysis of zinc demonstrated a very rapid dissolution of ZnO particles after deposition in the lungs. Statistically significant increases in Zn levels in the lungs were detectable only on day 1 post-exposure (NM-111). Overall, no relevant amounts of increased NM-111 in the ionic or particulate matter were detected in any body compartment. Amorphous silica (NM-200) particles were found in the cytoplasm of intraalveolar macrophages in the lung and the cytoplasm of macrophages in the lung associated lymph node. Interestingly, these particles were found in a few animals of all treatment groups (1, 2.5, and 5 mg/m3 NM-200) even after 91 days post-exposure. In all other organs of the NM-200 treated animals such as the nasal epithelium, trachea, larynx, liver, spleen, kidney, and mesenteric lymph node no particles were found at any time point investigated. Carbon black was tagged internally (“intrinsically”) with a γ tracer (7beryllium; half-time: 53.3 days). Due to limited amounts, the test item (0.3 mg per rat lung) was intratracheally instilled into the lungs. This dose avoided a particle overload effect, meaning that the toxicokinetic fate of carbon black could be followed under the approximated physiological conditions of lung clearance. Analysis of the γ labeled carbon black confirmed conclusively that there was no evidence for the translocation of carbon black beyond the lung into the blood or other body compartments. Very small amounts were only detected in lung-associated lymph nodes (LALN). On day 20 post-treatment, upon necropsy, both carbon black samples were practically exclusively found in lungs (75.1% and 91.0%, respectively) and in very small amounts in the lung-associated lymph nodes (LALN), i.e., ~0.5%. In the other organs/tissues, the test item was not significantly detectable. Separation of leukocytes and cell-free supernatant of a bronchoalveolar lavagate by centrifugation revealed that carbon black was completely located in the cell sediment, indicating total engulfment by alveolar macrophages. In conclusion, in occupational settings the nanomaterials titanium dioxide, zinc oxide, amorphous silica, and carbon black acted as microscaled agglomerates, not as individual nanoparticles. They displayed no potential to translocate beyond the lung into the blood compartment. Besides lungs, very small particulate amounts were detected only in LALN. This finding is consistent with the behavior of microscaled poorly soluble particles. Overall, there was no evidence of translocation of the nanomaterials following pulmonary exposures.